(untitled) (Swiss Medical Weekly, 2020)
BACKGROUND A clinical research application must be submitted for approval by a competent ethics committee (EC) before a study can be executed. There is very limited information on how such submissions could be optimised, especially regarding research in children and adolescents, which requires particular caution and age-adapted patient information. METHODS We assessed all research applications from the University Children’s Hospital Zurich submitted to the EC of the Canton of Zurich in 2014–2015, i.e., in the first two years after Switzerland’s new Human Research Act came into effect. Moreover, we validated our findings by assessing a randomly selected sample of applications from the same hospital in 2018–2019. RESULTS We assessed a total of 86 applications from 2014–2015, originating from 29 departments and sub-specialties. The EC judged that it was not responsible for three applications and declined an assessment for another three because the studies had already been conducted. Thus, we included 80 applications in the present analysis (18 clinical trials, 52 research projects, 10 further use projects). Applicants withdrew four applications before the EC’s final decision and the EC rejected two after assessment. The EC had objections in 46 (62%) of the remaining 74 applications. Formal, including formal legal, objections (n = 503) and legal objections (n = 287) accounted for the vast majority of objections. There were also 71 ethical and 82 scientific objections. The most frequent formal and formal legal objections were incomplete or missing age-adapted patient information (49%) and incorrect templates for informed consent and signature forms (46%). A review of the 20 randomly selected applications from 2018–2019 confirmed that four out of the five most frequent deficiencies relating to informed consent were identical to those observed in the 2014–2015 applications. CONCLUSIONS Careful preparation of submission documents by the investigators and close adherence to formal and legal requirements have the potential to considerably optimise and expedite the EC review process, and thus the commencement of the clinical research.